The Internet for weight control in an obese sample: results of a randomised controlled trial - Thomas James D; Greenwood Darren C; Harvey Emma L; Cockroft Jennie E; Kirk Sara FL; McConnon Áine; Ransley Joan K; Bojke Laura (BMC, 2007)
Abstract Background Rising levels of obesity coupled with the limited success of currently available weight control methods highlight the need for investigation of novel approaches to obesity treatment. This study aims to determine the effectiveness and cost-effectiveness of an Internet-based resource for obesity management. Methods A randomised controlled trial conducted in a community setting, where obese volunteers (n = 221) were randomly assigned to Internet group (n = 111) or usual care group (n = 110). Objective measures of weight and height were obtained. Questionnaires were used to collect dietary, lifestyle, physical activity and quality of life data. Data were collected at baseline, six months and 12 months. Results Data were collected on 54 (49%) participants in the Internet group and 77 (70%) participants in the usual care group at 12 months. Based on analysis conducted on all available data, the Internet group lost 1.3 kg, compared with 1.9 kg weight loss in the usual care group at 12 months, a non-significant difference (difference = 0.6 kg; 95% CI: -1.4 to 2.5, p = 0.56). No significant differences in change in secondary outcome measures between the two groups at six or 12 months were revealed. Total costs per person per year were higher in the Internet group than the usual care group (£992.40 compared to £276.12), primarily due to the fixed costs associated with setting up the website, and QALYs were similar (0.78 and 0.77) for both groups. Conclusion This trial failed to show any additional benefit of this website in terms of weight loss or secondary outcome measures compared with usual care. High attrition and low compliance limits the results of this research. The results suggest that the Internet-based weight control resource was not a cost-effective tool for weight loss in the obese sample studied. Trail Registration ISRCTN 58621669